2011
DOI: 10.1182/blood.v118.21.182.182
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Antibody Responses Depend on CD28 Function in Bone Marrow Resident Plasma Cells

Abstract: 182 Protective immunity against infection requires sustained antibody production by long-lived plasma cells (LLPC) that survive for years/decades within specialized niches. What regulates/supports this survival remains largely unknown. However, it has been shown that normal and transformed (human multiple myeloma) LLPC are critically dependent on the bone marrow microenvironment, including cell-to-cell interactions. This lead us to hypothesize that modulating these interactions could either enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 0 publications
6
56
1
Order By: Relevance
“…23 Genes such as BLIMP-1, Myeloid cell leukemia 1 (MCL1), CD28, and B-cell maturation antigen (BCMA), which are essential for the long-term survival of plasma cells, were similarly expressed transcriptionally across all mature mouse plasma cells irrespective of their longevity. 1,23,105,[132][133][134][135] In previous work, we and others demonstrated that the transcription factor ZBTB20 promotes plasma cell longevity. 136,137 Reciprocally, ZBTB32, a related family member, antagonizes plasma cell longevity.…”
Section: A Me Taboli C E Xpl Anati On For Pl a S Ma Cell Long E Vit Ymentioning
confidence: 90%
See 1 more Smart Citation
“…23 Genes such as BLIMP-1, Myeloid cell leukemia 1 (MCL1), CD28, and B-cell maturation antigen (BCMA), which are essential for the long-term survival of plasma cells, were similarly expressed transcriptionally across all mature mouse plasma cells irrespective of their longevity. 1,23,105,[132][133][134][135] In previous work, we and others demonstrated that the transcription factor ZBTB20 promotes plasma cell longevity. 136,137 Reciprocally, ZBTB32, a related family member, antagonizes plasma cell longevity.…”
Section: A Me Taboli C E Xpl Anati On For Pl a S Ma Cell Long E Vit Ymentioning
confidence: 90%
“…132,133 A number of other extrinsic stimuli, such as IL-6 and Tumor Necrosis Factor α, and engagement of CD28 and CD44 also promote plasma cell survival ex vivo. 134,177,178 Genetic knockout studies, however, have provided mixed results, suggesting that plasma cell-intrinsic signaling by these factors might not all be essential in vivo. 133,179 A number of accessory cell types such as eosinophils, basophils, megakaryocytes, regulatory T cells, and mesenchymal cells have all been proposed to enhance plasma cell survival.…”
Section: Cell Extrinsic Factorsmentioning
confidence: 99%
“…There is also evidence for the intrinsic function of CD28 in the survival of plasma cells [24]. Loss of CD28 or its ligands B7-1 and B7-2 results in altered frequency of plasma cells and antibody levels, although debate remains as to whether CD28 is a positive or negative regulator of plasma cells [25,26]. In this study, we provide evidence that B cells contribute to the pathogenesis of SAP in B7-2 KO NOD mice, irrespective of the complex sequelae of B7-2 elimination on humoral immunity.…”
Section: Introductionmentioning
confidence: 99%
“…CD28 deficiency in the B cell compartment only affects the maintenance of plasma cell in the bone marrow. The threshold for CD28-dependent NF-B activation is much lower in bone marrow plasma cells compared to splenic plasma cells [42]. Because CD80 (a ligand for CD28) is expressed on CXCL12 hi reticular cells, bone marrow plasma cells might obtain significant survival advantage by their interaction with the CXCL12 hi reticular cells.…”
Section: Niches In the Bone Marrowmentioning
confidence: 99%